CADANGAN FULL PRELIMINARY TERM ASURANSI DWIGUNA DENGAN HUKUM DE MOIVRE - Sherly Mutya Faradilla; Hasriati '; Tumpal Parulian Nababan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper discusses premium reserve endowment life insurance for years. The reserve is calculated by the method of full preliminary term based on net annual premium, with the first net annual premium and the second net annual premium . Net annual premium is affected by amount of single premium and annuity due. De Moivre law is applied to calculate the reserve.